Key factor on improving secondary advanced dewatering performance of municipal dewatered sludge: Selective oxidative decomposition of polysaccharides. (June 2020) - Lin, Naixi; Zhu, Wei; Fan, Xihui; Wang, Chenyu; Chen, Cheng; Zhang, Hao; Chen, Le; Wu, Silin; Cui, Yan
Abstract: Advanced dewatering technologies with moisture content from nearly 80% to below 60% have attracted widespread attention in the field of municipal dewatered sludge disposal. The usage of the correct types of oxidants and the degradation of key component on the effect of secondary advanced dewatering performance is a rising focus. In this study, three types of typical oxidants (Fenton's reagent, H2 O2, and KMnO4 ) were used to pre-treat dewatered sludge directly, then advanced dewatering performance, conversion rate of bio-bound water and decomposition trend of various organic biomass were analysed. Results showed that final moisture content of Fenton's reagent group reduced to below 50% with exposure to the compression of 1000 kPa for 30 min. Different oxidants that were characterized by selective oxidizability and, compared with other oxidants, mainly decomposed proteins, lipids and humic substances, the key component of polysaccharides, which may combine with the most water were primarily decomposed by Fenton's reagent. This promoted the conversion from bio-bound water to free water and advanced dewatering performance significantly. From a morphological perspective, the ratio of dissolved polysaccharides from three layers showed Pellets: tightly bound EPS (T-EPS): loosely bound EPS (L-EPS) = 52.28%–66.56%: 8.37%–12.75%: 23.15%–39.08%, and due to the cell-breaking capacity, Fenton's reagent could mainly promote the release of intracellular polysaccharides-bound water. Highlights: Effect of oxidants on secondary advanced dewatering for dewatered sludge directly explored. TOC reduction could not enhance conversion of bound water predicatively. Key component enhances advanced dewatering confirmed. Release of intracellular polysaccharide-bound water promoted by Cell-breaking capacity of Fenton's reagent. Polysaccharides would be oxidized selectively by Fenton's reagent.